Akulturasi Arsitektur Kolonial Belanda pada Rumah Toko Cina Peranakan di Jakarta - Christianto Roesli; Sri Rachmayanti (Humaniora, 2014)
Indonesia is a nation consisting of various ethnicities, races, and cultures. It is because the location of the Indonesian archipelago was in the traffic trade in the early days of the 5th century AD. Chinese ethnic is one ethnicity that already has had a relationship with the Southeast Asian region. In the 19th century shop houses were spread in the coastal areas and concentrated only in the Chinatown. Research used qualitative method with a historical approach. Data were obtained from a variety of literature, both journal articles, books, and the Internet. The results show that in the beginning the shop houses were built by the colonial government to implement a plot system such in the Europe. However, by the influence of the Chinese descendants, limited land with a high population density makes the system become a clever problem solving. Acculturation is a process that refers to the cultural and psychological changes due to encounters with culturally different people. This process allows culture and ethnic groups adapt to another culture. Research concludes that shop house can be seen as a result of Chinese descendants and Dutch acculturation existing in the coastal cities of Indonesia.